Cystatin c – a marker of kidney function and predictor of cardiovascular disease and mortality: Cistatin c – označevalec ledvičnega delovanja ter napovedovalec srčnožilnih bolezni in umrljivosti - Bevc, Sebastjan; Ekart, Robert; Hojs, Radovan (Acta Medico-Biotechnica, 2021)
Over the past decade, serum cystatin C (SCC) has been often suggested as a marker of kidney function. Strong evidence has shown that SCC may improve classification of the glomerular filtration rate (GFR) to identify chronic kidney disease in certain clinical populations. SCC equations based on the SCC reference standard are considered state–of–the–art to estimate kidney function and the latest chronic kidney disease guidelines included several suggestions and recommendations that relate to SCC. The results of several previous studies have also suggested that SCC may be more useful than just a marker of GFR, as it may also be useful as a clinical marker to provide complementary information to established risk determinants, especially for high–risk populations. Additionally, other studies have reported that SCC may be a useful prognostic indicator of cardiovascular disease.